1995
DOI: 10.1055/s-0038-1653783
|View full text |Cite
|
Sign up to set email alerts
|

Association of Variables of Coagulation, Fibrinolysis and Acute-phase with Atherosclerosis in Coronary and Peripheral Arteries and those Arteries Supplying the Brain

Abstract: SummaryWe investigated the vessel status of coronary and peripheral arteries and those arteries supplying the brain in 929 consecutive male patients admitted to a coronary rehabilitation unit. The severity of coronary atherosclerosis was scored using coronary angiography. Changes in extracranial brain vessels and manifest cerebrovascular disease (CVD) were determined by B-mode ultrasound and Doppler examination. Peripheral arterial disease (PAD) was diagnosed using base-line and stress oscillography. We assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
1
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(97 citation statements)
references
References 41 publications
(24 reference statements)
2
89
1
5
Order By: Relevance
“…9 These studies were followed by several angiographic series and by cross-sectional and case-control studies, suggesting that CRP concentrations correlated directly with the presence and severity of coronary, cerebral, and peripheral arterial atherosclerosis. [10][11][12] In addition, various studies examined CRP concentrations among patients with angina pectoris. Liuzzo et al 13 reported that in patients admitted to the hospital with acute unstable angina, CRP levels above 3 mg/l were associated with a significantly worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…9 These studies were followed by several angiographic series and by cross-sectional and case-control studies, suggesting that CRP concentrations correlated directly with the presence and severity of coronary, cerebral, and peripheral arterial atherosclerosis. [10][11][12] In addition, various studies examined CRP concentrations among patients with angina pectoris. Liuzzo et al 13 reported that in patients admitted to the hospital with acute unstable angina, CRP levels above 3 mg/l were associated with a significantly worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…8 A third acute-phase reactant of interest is fibrinogen. 9,10 Numerous workers have reported an increase in fibrinogen in atherosclerosis, 11,12 but it is unclear whether this elevation is mainly a cause or a result of the disease, although both may be true. The acute-phase response is under tight control of interleukin 6 (IL-6), 13 which is produced to a large extent by macrophages.…”
mentioning
confidence: 99%
“…IL-6 may thus be pivotal in the putative inflammatory pathogenesis of coronary disease. Inflammatory markers are associated with the development of coronary disease, with disease severity, 13 and with the occurrence of coronary events. 14 Data from the Physicians Health Study suggest that this association is still present after an 8-year follow-up period, 15 implying that progression of atheroma may also be associated with raised inflammatory markers.…”
mentioning
confidence: 99%